For this case we have a function of the form
![y = f (x).](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ewx8nwyjjtugvrwj2ny2n06x38ookaujnz.png)
Where:
![f (x) = 2x ^ 2 + 3x + 5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lofogfd8yka12bt3ie4i21bp1625qqom3x.png)
They tell us that the function has a value of 19, and we want to know the values of the input, that is:
![2x ^ 2 + 3x + 5 = 19\\2x ^ 2 + 3x + 5-19 = 0\\2x ^ 2 + 3x-14 = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lyl5n2fvwslvy3kfkkavlxzq8m6nsuygfv.png)
We apply the formula of the resolvent:
![a = 2\\b = 3\\c = -14](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vzno3zdhvz8kunvsmh40nq9l8jt7cccn3i.png)
![x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2 (a)}\\x = \frac {-3 \pm \sqrt {3 ^ 2-4 (2) (- 14)}} {2 (2)}\\x = \frac {-3 \pm \sqrt {9 + 112}} {4}\\x = \frac {-3 \pm \sqrt {121}} {4}\\x = \frac {-3 \pm11} {4}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fk0rmqgb243adj0xokt2ohqdpd1e2bewzj.png)
We have two roots:
![x_ {1} = \frac {-3 + 11} {4} = \frac {8} {4} = 2\\x_ {2} = \frac {-3-11} {4} = \frac {-14} {4} = - \frac {7} {2}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/oibdwjezmcgwzuz8jso2j4u1jb8inu9ybs.png)
Answer:
The inputs of the function
are:
![x_ {1} = 2\\x_ {2} = - \frac {7} {2}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qx7fawwbbo438v8rcp7z6ksqhzrh7s02bw.png)